Are new supraglottic airway devices, tracheal tubes and airway viewing devices cost‐effective?. Issue 1 (5th November 2014) - Slinn, Simon J.; Froom, Stephen R.; Stacey, Mark R. W.; Gildersleve, Christopher D.; Morton, Neil
Summary Over the past two decades, a plethora of new airway devices has become available to the pediatric anesthetist. While all have the laudable intention of improving patient care and some have proven clinical benefits, these devices are often costly and at times claims of an advantage over current equipment and techniques are marginal. Supraglottic airway devices are used in the majority of pediatric anesthetics delivered in the UK, and airway‐viewing devices provide an alternative for routine intubation as well as an option in the management of the difficult airway. Yet hidden beneath the convenience of the former and the technology of the latter, the impact on basic airway skills with a facemask and the lack of opportunities to fine‐tune the core skill of intubation represent an unrecognised and unquantifiable cost. A judgement on this value must be factored into the absolute purchase cost and any potential benefits to the quality of patient care, thus blurring any judgement on cost‐effectiveness that we might have. An overall value on cost‐effectiveness though not in strict monetary terms can then be ascribed. In this review, we evaluate the role of these devices in the care of the pediatric patient and attempt to balance the advantages they offer against the cost they incur, both financial and environmental, and in any quality improvement they might offer in clinical care.